Economic Analysis of Hybrid Power Plant (Solar-Diesel) on Kawaluso Island, North Sulawesi - Ilham Amba , Muhammad; Dalimi, Rinaldy (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2023)
Kawaluso Island is one of the outermost islands in Indonesia with a distance of 68 KM from the city of Tahuna or 5-10 hours by boat from the capital of the Sangihe Islands Regency, Tahuna. Currently, electricity on Kawaluso Island is supplied by a diesel power plant (PLTD) with a capacity of 200 kW. This condition causes Kawaluso Island to be electrified 12 hours per day. So that additional sources of power plant are needed so that the electricity on Kawaluso Island is on 24 hours a day. Therefore, a solar power plant (PLTS) is one of alternative as additional power for Kawaluso Island and reduces the cost of production. A diesel power plant where the price of industrial fuel reaches up to Rp. 24.500 and it make Cost of Energy Rp. 10.360/kWh. The method used in this study uses the Levelized Cost of Energy (LcoE) method. The results of the analysis show that the hybrid between diesel power plant and solar power plant 64 kWp and 72 kWp has a Life Cycle Cost (LCC) value of Rp24.389.601.114,40 and Rp. 20.589.498.278,40 With a Cost of Energy (COE) of Rp. 7.432 and Rp. 5.601/kWh. Net Present Value (NPV) obtained is positive. And the payback period is 3 and 9 years of investment and is categorized as feasible to continue.